Changes in structure and symptoms in knee osteoarthritis and prediction of future knee replacement over 8 years. - Bruyere, O; Cooper, C; Pavelka, K; Rabenda, V; Buckinx, F; Beaudart, C; Reginster, J (2013)
The objective of this study was to assess the association between changes in joint space width (JSW, i.e., structure) or Western Ontario and McMaster Universities (WOMAC) score (i.e., symptoms) over 3 years in patients with knee osteoarthritis and the occurrence of knee replacement over 8 years. We followed 133 subjects with primary knee osteoarthritis prospectively for a mean of 8 years. JSW (standard radiography) and symptoms (total WOMAC score) were assessed every year for 3 years. The rate of knee replacement was recorded for the following 5 years. Logistic regressions were performed according to the intention-to-treat principle. After 8 years' follow-up, ten patients (7.5 %) had undergone a knee replacement. The changes in JSW or WOMAC score over 3 years were significantly associated with the occurrence of knee replacement during the following 5 years (p = 0.02 and p = 0.03, respectively). Each 0.1-mm narrowing of JSW over 3 years was associated with a 14 % (95 % CI 3-25 %) increased risk for knee replacement. For every 10 % increase in WOMAC score, the risk for joint replacement was increased by 16 % (95 % CI 1-33 %). When JSW and WOMAC score were included in the same statistical model, they were still significantly associated with risk for knee replacement (p = 0.02 and p = 0.03, respectively), but JSW change was the only variable that remained significant after adjusting for all potential confounders. Our results suggest that changes in symptoms and, more particularly, in structure over 3 years in patients with osteoarthritis reflect a clinically relevant progression of the disease.